Association of COPD with adverse outcomes in heart failure patients with preserved ejection fraction - Shuo Xu; Zhenbang Gu; Wengen Zhu; Shenghui Feng (ESC Heart Failure)
Abstract We performed a systematic review and meta‐analysis to detect the impact of chronic obstructive pulmonary disease (COPD) on the prognosis of heart failure patients with preserved ejection fraction (HFpEF). We systematically screened eligible literature from three electronic databases, PubMed, EMBASE and Cochrane Library, up to April 2023. Two researchers participated in data collection independently. Risk ratios (RRs) from included studies with 95% confidence intervals (CIs) were pooled in the Review Manager version 5.40 software using a random‐effects model for analysis. A total of 11 studies (3 post hoc analyses of RCTs and 8 observational studies) with 18 602 participants were included in this meta‐analysis. After pooling all the data from eligible studies, our results indicated that COPD was associated with an increased risk of hospitalization (RR = 1.66, 95% CI, 1.47–1.87, P < 0.00001), mortality (RR = 1.62, 95% CI, 1.34–1.95, P < 0.00001), and the composition of hospitalization or mortality (RR = 1.84, 95% CI, 1.35–2.51, P < 0.001) in patients with HFpEF. In a subgroup analysis, the risks of cardiovascular‐related mortality (RR = 1.59, 95% CI, 1.30–1.93, P < 0.00001) and post‐discharge mortality risk (RR = 2.57, 1.34–4.93, P < 0.01) were increased in HFpEF patients comorbid with COPD, and these associations were also detected in HF‐caused hospitalization (RR = 1.64, 95% CI, 1.44–1.87, P < 0.00001). Evidence from existing studies supported that COPD was an independent prognostic risk factor for patients with HFpEF. Developing rapid clinical diagnostic indicators and early use of novel drugs such as SGLT‐2 and ARNI may improve the prognosis of this population, deserving further study.